A scoping review of patient-centred tuberculosis care interventions: Gaps and opportunities. - Hanlie Myburgh; Dzunisani Baloyi; Marian Loveday; Sue-Ann Meehan; Muhammad Osman; Dillon Wademan; Anneke Hesseling; Graeme Hoddinott (Public Library of Science (PLoS), 2023)
Tuberculosis (TB) is a leading cause of death globally. In 2015, the World Health Organization hailed patient-centred care as the first of three pillars in the End TB strategy. Few examples of how to deliver patient-centred care in TB programmes exist in practice; TB control efforts have historically prioritised health systems structures and processes, with little consideration for the experiences of people affected by TB. We aimed to describe how patient-centred care interventions have been implemented for TB, highlighting gaps and opportunities. We conducted a scoping review of the published peer-reviewed research literature and grey literature on patient-centred TB care interventions between January 2005 and March 2020. We found limited information on implementing patient-centred care for TB programmes (13 research articles, 7 project reports, and 19 conference abstracts). Patient-centred TB care was implemented primarily as a means to improve adherence, reduce loss to follow-up, and improve treatment outcomes. Interventions focused on education and information for people affected by TB, and psychosocial, and socioeconomic support. Few patient-centred TB care interventions focused on screening, diagnosis, or treatment initiation. Patient-centred TB care has to go beyond programmatic improvements and requires recognition of the diverse needs of people affected by TB to provide holistic care in all aspects of TB prevention, care, and treatment.